2018
DOI: 10.1038/s41467-018-04627-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and widespread white matter plasticity during an intensive reading intervention

Abstract: White matter tissue properties are known to correlate with performance across domains ranging from reading to math, to executive function. Here, we use a longitudinal intervention design to examine experience-dependent growth in reading skills and white matter in grade school-aged, struggling readers. Diffusion MRI data were collected at regular intervals during an 8-week, intensive reading intervention. These measurements reveal large-scale changes throughout a collection of white matter tracts, in concert wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(168 citation statements)
references
References 76 publications
11
148
3
Order By: Relevance
“…Note that findings from tractography studies using AFQ software are mostly consistent with our findings in reporting negative correlations between FA and reading (Huber, Donnelly, Rokem, & Yeatman, ; Travis, Ben‐shachar, Myall, & Feldman, ; Yeatman, Dougherty, Ben‐shachar, & Wandell, ). Particularly interesting are findings from a longitudinal study by Yeatman, Dougherty, Ben‐shachar, and Wandell (): At the onset of the study, when children were aged 7–12, above‐average readers had lower FA than below‐average readers in the left AF and ILF.…”
Section: Discussionsupporting
confidence: 88%
“…Note that findings from tractography studies using AFQ software are mostly consistent with our findings in reporting negative correlations between FA and reading (Huber, Donnelly, Rokem, & Yeatman, ; Travis, Ben‐shachar, Myall, & Feldman, ; Yeatman, Dougherty, Ben‐shachar, & Wandell, ). Particularly interesting are findings from a longitudinal study by Yeatman, Dougherty, Ben‐shachar, and Wandell (): At the onset of the study, when children were aged 7–12, above‐average readers had lower FA than below‐average readers in the left AF and ILF.…”
Section: Discussionsupporting
confidence: 88%
“…There is considerable evidence that experience or training can alter white‐matter FA. For example, increased FA in target tracts has been demonstrated in response to juggling training (Scholz, Klein, Behrens, & Johansen‐Berg, ), meditation training (Tang et al, ), cognitive training (Mackey, Whitaker, & Bunge, ), learning to read (Carreiras et al, ; Hofstetter, Friedmann, & Assaf, ; Thiebaut de Schotten, Cohen, Amemiya, Braga, & Dehaene, ), and following reading intervention (Keller & Just, ; Huber, Donnelly, Rokem, & Yeatman, ; Hofstetter et al, ). For example, in a study of adults, learning Morse code was associated with a significant increase in left ILF FA (Schlaffke, Leemans, Schweizer, Ocklenburg, & Schmidt‐Wilcke, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of adults, learning Morse code was associated with a significant increase in left ILF FA (Schlaffke, Leemans, Schweizer, Ocklenburg, & Schmidt-Wilcke, 2017). In another study, rapid changes in white matter properties of the left ILF, among other tracts, were demonstrated in children with dyslexia in response to an intensive reading intervention (Huber et al, 2018). Importantly, the effects of parental practices (e.g., quality of nutrition, conflict in the household, and verbal abuse) on white matter structure in early childhood have been shown (Choi, Jeong, Rohan, Polcari, & Teicher, 2009;Dufford & Kim, 2017;Lebel et al, 2016;Ou et al, 2014).…”
Section: Association Between Ses and (Pre-)literacy Performancementioning
confidence: 98%
“…Understanding maturational changes in plasticity that occur over the course of elementary school is an important scientific challenge with practical implications for education practice. Our previous work established an experimental paradigm (intensive, one-on-one reading intervention program) and measurement protocol (longitudinal diffusion MRI measurements) for quantifying experience-dependent plasticity in human white matter (Huber et al, 2018). A power analysis based on these data confirmed that we have the statistical power to detect meaningful maturational differences in experiencedependent plasticity, if such differences exist (see Figure 1).…”
Section: Pre-registrationmentioning
confidence: 68%
“…Two principal challenges to studying experience-dependent plasticity in humans are, first, establishing an experimental paradigm that is appropriate for human research subjects and capable of inducing largescale structural changes in the brain and, second, developing non-invasive measurements that are sensitive to changes in cellular properties of human brain tissue. Our previous work demonstrated that combining an intensive reading intervention program with longitudinal diffusion-weighted magnetic resonance imaging (dMRI) measurements in children with dyslexia is a powerful paradigm for studying experience-dependent changes in the white matter (Huber et al, 2018). In a sample of 24 children between 7 and 13 years of age, eight weeks of targeting training in reading skills caused large-scale changes in tissue properties for multiple anatomical tracts (Cohen's d = 0.5-1.0 across different white matter tracts), that were coupled to large improvements in reading skills (Cohen's d = 0.5-1.0 across different reading tests).…”
Section: Introductionmentioning
confidence: 99%